The art of learning with passion. How college students learn when they study with passion (Encuentros, 2016)
This article shows the results of the research “Degree of assertiveness of officials in the public administration of the municipality of Montería customer”. The objective of this study is to evaluate the style of assertiveness that officials use to face different social situations, respond to criticism and solve problems. The population consisted of fifteen (15) staff members between 30 and 55 years of age who work in human resources, Secretary of the Treasury and Sisben dependencies. The methodological design was descriptive, transversal with a quantitative approach. The assessment tool that was used was the multidimensional scale of assertiveness. The results obtained show a deficit in assertive behaviors in officials.Keywords: assertiveness, indirect assertiveness, non-assertiveness, customer service